Strategic Entrepreneurship: Integrating Entrepreneurial and Strategic Management Perspectives, a Case Study at Pesantren Tebuireng Jombang, East Java - Arifyanto, A Fakhri; Salim, Ubud; ., Sudjatno; ., Rofiaty (KnE Social Sciences, 2021)
This study examines Pesantren (Islamic boarding schools) as institutions of education and religion, especially during the global and digital era. A central question concerns how Pesantren position themselves as traditional religious schools or follow the process of modernization, for example by enhancing their curriculum and changing their governance. This depends on the management model and leadership applied by the kyai (religious leader) in Pesantren in response to the changing era. In general, the leadership of Pesantren still adopt a centralized and hierarchical pattern placing the kyai as their central figure. A kyai with charismatic attainment organizes the Pesantren using his skills and knowledge. Research on the role of entrepreneurial and strategic leadership of kyais in Pesantren has been fragmented. This paper therefore examines the significance of the entrepreneurial leadership role of Kyai Salahudin Wahid in cultivating the transformational and entrepreneurial leadership spirit of Pesantren Tebuireng Jombang. The conceptual framework is focused on the development of a strategic human resources management framework which is then extended into the context of Pesantren, entrepreneurial leadership, and a strategic management perspective. Keywords: Strategic Entrepreneurship, Entrepreneurial Leadership, Pesantren, Kyai